2022
DOI: 10.1002/jsfa.11733
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding mechanism of ferulic acid and ovalbumin: insights from spectroscopy, molecular docking and dynamics simulation

Abstract: BACKGROUND: Ferulic acid (FA), a phenolic acid widely occurring in nature, has attracted extensive attention because of its biological activity. Ovalbumin (OVA) is a commonly used carrier protein. The mechanism of FA binding with OVA was investigated by utilizing a variety of spectral analyses, accompanied by computer simulation. RESULTS: It was discovered that the fluorescence quenching mechanism of OVA by FA was a static mode as a result of the formation of an FA−OVA complex, which was verified by the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…The numbers of hydrogen bonds within 100 ns during MD were recorded in Figure 5C, illustrating that there were 1-3 hydrogen bonds maintained between FA and PZ during the MD process. The results were in accordance with the form research, which had shown 2-3 hydrogen bonds between PZ and curcumin, and 0-4 hydrogen bonds between ovalbumin and FA [25,46]. As one of the main non-covalent interactions, hydrogen bonds play a crucial role in non-covalent interactions of the PZ-FA complex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The numbers of hydrogen bonds within 100 ns during MD were recorded in Figure 5C, illustrating that there were 1-3 hydrogen bonds maintained between FA and PZ during the MD process. The results were in accordance with the form research, which had shown 2-3 hydrogen bonds between PZ and curcumin, and 0-4 hydrogen bonds between ovalbumin and FA [25,46]. As one of the main non-covalent interactions, hydrogen bonds play a crucial role in non-covalent interactions of the PZ-FA complex.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the leading contribution of PZ-FA binding is van der Waals energy (−28.88 ± 2.04 kcal/mol), followed by electrostatic energy (−21.30 ± 2.77 kcal/mol), and then the non-polar contribution to solvation (−4.61 ± 0.05 kcal/mol). This result correlated well with the ovalbumin-FA interactions, and its binding free energy reached −26.78 kcal/mol [46]. For further analysis of binding energy, we explored the contribution of amino acids to binding.…”
Section: Discussionsupporting
confidence: 63%
“…Molecular simulation can directly display the binding mode of small molecule ligands with XO [32] . Figure 7 A and D respectively showed the optimal binding sites of quercetin and kaempferol with XO after 100 times of docking.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking was performed with the Discovery Studio 3.5 program. 19 The crystal structure of OVA (code 1OVA) was acquired from the RCSB Protein Data Bank (http://www.rcsb.org/ structure/1OVA) and was treated by adding Gasteiger charges and polar hydrogen atoms to obtain the monomer OVA used for molecular docking. Next, the molecular model of RES (Pubchem CID: 445154) was downloaded from the Pubchem website.…”
Section: Molecular Dockingmentioning
confidence: 99%